Distribution of citrate and citrate infusion rate during donor plasmaphereses - Evers, Josef; Taborski, Uwe (Journal of clinical apheresis, 2016)
Background: The purpose of this study was to describe the distribution of trisodium‐citrate 4% (TSC) anticoagulant (AC) between the product and the donors undergoing plasma donation. Subjects and Methods: Data of 32 regular donors of plasma initially collected for a study published in 2010 were re‐analyzed to determine the amount of citrate received by the donor and the citrate infusion rate (CIR) in mg/kg/min to the donor. Donor plasmaphereses (DP) were performed with the automated Haemonetics plasma collecting system 2 (PCS2). Plasma volume was programmed at 760 ml including AC. CIR was calculated from citrate received by the donors divided by the body weight over time. Results: 130 ± 12 ml TSC was used for 760 ml plasma. An average of 110 ml TSC or 84.6% of citrate load was in collected plasma and not given to the donor. From the difference of 20 ml or 514 mg citrate an average CIR of 0.16 mg/kg/min was calculated. Conclusion: The total amount of citrate received by the donor is minimal and the average CIR is below the critical level of 1 mg/kg/min. J. Clin. Apheresis 31:59–62, 2016. © 2015 Wiley Periodicals, Inc.